Solar Energy 2006
DOI: 10.1115/isec2006-99079
|View full text |Cite
|
Sign up to set email alerts
|

A Zero Carryover Liquid-Desiccant Air Conditioner for Solar Applications

Abstract: A novel liquid-desiccant air conditioner that dries and cools building supply air has been successfully designed, built and tested. The new air conditioner will transform the use of direct-contact liquid-desiccant systems in HVAC applications, improving comfort and indoor air quality, as well as providing energy-efficient humidity control. Liquid-desiccant conditioners and regenerators are traditionally implemented as adiabatic beds of contact media that are highly flooded with desiccant. The possibility of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 2 publications
0
59
0
Order By: Relevance
“…A machine at almost commercial level, using CaCl 2 aqueous solution as liquid desiccant has been reported by Lowenstein et al [87,95] who have been investigating the process since 1988. The proposed design of liquid desiccant air-conditioner, which has been tested in several locations under full scale operation, is given in Fig.…”
Section: Selected Examples Of the Use Of Cacl 2 For Dehumidification mentioning
confidence: 99%
See 2 more Smart Citations
“…A machine at almost commercial level, using CaCl 2 aqueous solution as liquid desiccant has been reported by Lowenstein et al [87,95] who have been investigating the process since 1988. The proposed design of liquid desiccant air-conditioner, which has been tested in several locations under full scale operation, is given in Fig.…”
Section: Selected Examples Of the Use Of Cacl 2 For Dehumidification mentioning
confidence: 99%
“…Indeed, the researchers consider that LiCl and CaCl 2 aqueous solutions are the most viable liquid desiccant for solar applications [87]. However, the operation of the proposed machine with CaCl 2 aqueous solution leads to a more cost effective machine than when LiCl aqueous solution is used, though LiCl aqueous solution provides higher dehumidification than CaCl 2 aqueous solution [95].…”
Section: Selected Examples Of the Use Of Cacl 2 For Dehumidification mentioning
confidence: 99%
See 1 more Smart Citation
“…The COP of the regenerator was found to be 0.93 when concentrating a solution of lithium chloride from 36% to 40% and supplied with hot fluid at 93.3•C. Figure 11 A 6,000 cfm low-flow liquid-desiccant conditioner 41 When using CFC or HCFC as refrigerants in liquid desiccant cooling systems, the generator temperature has to be above 150•C. If solar energy is used as main driving force for the system, the solar collector has to be of the evacuated tube type instead of a simple flat plate collector, this will definitely lead to higher costs.…”
Section: Liquid Desiccant Cooling Applicationmentioning
confidence: 99%
“…The testing results demonstrated that at a heat exchanger angle of 45•, there was an optimum value of air mass flow rate at which the effectiveness and dehumidification efficiency of the plate heat exchanger were maximized. Figure 10 Schematic diagram of the cross-flow type plate heat within the absorber are the simultaneous steady-exchanger 63,64 Another low-flow liquid desiccant conditioner using a plastic-plate heat exchanger was presented by Lowenstein et al 41 . The cross section of the plate (as shown in Figure 11) was 2.5mm by 305mm, with 110 cooling passages running the length of the extrusion.…”
Section: Liquid Desiccant Cooling Applicationmentioning
confidence: 99%